Variación socioeconómica de los rasgos fonéticos dialectales de la lengua española - Coloma, Germán (2011)
This paper tries to quantify the socioeconomic importance of seven phonetic characteristics (seseo, yeismo, /s/-aspiration, /x/-aspiration, /?/-assibilation, /r/-assibilation, and /n/-velarization) whose presence or absence allows distinguishing among twenty-four Spanish dialects. In order to accomplish this goal, we perform a least-square regression analysis to calculate “hedonic prices” for the abovementioned characteristics. The result is that the three more significant characteristics, which seem to operate as signs of a lower per-capita income, are seseo, /x/-aspiration and /r/-assibilation. The first of those characteristics keeps its statistical significance as a sociolinguistic marker when we restrict our analysis to the case of Spain, while /r/-assibilation keeps its statistical significance when we restrict our database to Colombian observations.